Nutritional status and hemoglobin level according to the type of breastfeeding in the 6-month-old infant - Buitron Martel, Esperanza Luz (2021)
Objective. To determine the relationship between nutritional status and hemoglobin level; type of breastfeeding and nutritional status; type of breastfeeding and hemoglobin level of the 6-month-old infant who attended the CRED control of the Centro de Salud Perú-Corea, Huánuco, 2019. Methods. It was a quantitative, retrospective, analytical and cross-sectional study. The sample population was 564 clinical histories of 6-month-old infants. The hypothesis test was based on the chi square test of independence, considering a p <= 0,05. Results. Evaluating the type of breastfeeding consumed by the 6-month-old infants, it was found that 65.6 % (370) continued with exclusive breastfeeding, compared to 25.7 % (145) with mixed breastfeeding. The nutritional status was normal in a higher proportion [99.1 % (559)]. The nutritional status was normal in a higher proportion [99.1 % (559)]. The hemoglobin level was also mostly normal [98.9 % (558)]. A relationship was found between nutritional status and hemoglobin level [(x2 = 488.13; p=0.000)], exclusive breastfeeding and normal nutritional status [(x2 = 25.55; p = 0.006)] and exclusive breastfeeding and normal hemoglobin level [(x2 =30.71; p = 0.000)]. Conclusions. There is a relationship between normal nutritional status and normal hemoglobin level, exclusive breastfeeding and normal nutritional status; likewise, a relationship was found between exclusive breastfeeding and normal hemoglobin level in infants.